STRATEGI KOMUNIKASI PT. MITRA INOVASI GEMILANG DALAM MENYAMPAIKAN PESAN IKLAN MELALUI MOBILE LED MING(Studi Kasus Mobile LED MING dari PT. Mitra Inovasi Gemilang) - Mutia Nella Rahmayanti (2020)
As technology develops, the media for advertising a product also continues to grow. One of them is a Light Emitting Diode (LED) Display that is attached to the vehicle body, which is a mini bus made by PT. Mitra Inovasi Gemilang. This study aims to determine the Communication Strategy Of PT. Mitra Inovasi Gemilang In Delivering Advertising Messages Via Mobile LED MING. This research uses descriptive qualitative method with a case study approach. Data collection is done by in-depth interviews and documentation. The results of the research show that in making the communication strategy of the use of mobile LED MING uses three stages, namely the formulation of strategies, implementation of strategies and evaluation of strategies with the aim of providing informative, persuasive and coercive messages. This has the aim to influence other companies to advertise and for audiences to buy products that have been presented in the mobile LED MING.